Bovine Milk Lactoferrin Selectively Kills Highly Metastatic Prostate Cancer PC-3 and Osteosarcoma MG-63 Cells In Vitro - Guedes, Joana P.; Pereira, Cátia S.; Rodrigues, Lígia R.; Côrte-Real, Manuela (Frontiers in Oncology, 2018)
Prostate cancer and osteosarcoma are the second most common type of cancer affecting men and the fifth most common malignancy among adolescents, respectively. The use of non-toxic natural or natural-derived products has been one of the current strategies for cancer therapy, owing to the reduced risks of induced-chemoresistance development and the absence of secondary effects. In this perspective, lactoferrin (Lf), a natural protein derived from milk, emerges as a promising anticancer agent due to its well-recognized cytotoxicity and anti-metastatic activity. Here, we aimed to ascertain the potential activity of bovine Lf (bLf) against highly metastatic cancer cells. The bLf effect on prostate PC-3 and osteosarcoma MG-63 cell lines, both displaying plasmalemmal V-ATPase, was studied and compared with the breast cancer MDA-MB-231 and the non-tumorigenic BJ-5ta cell lines. Cell proliferation, cell death, intracellular pH, lysosomal acidification, and extracellular acidification rate were evaluated. Results show that bLf inhibits proliferation, induces apoptosis, intracellular acidification, and perturbs lysosomal acidification only in highly metastatic cancer cell lines. By contrast, BJ-5ta cells are insensitive to bLf. Overall, our results establish a common mechanism of action of bLf against highly metastatic cancer cells exhibiting plasmalemmal V-ATPase. This study opens promising perspectives for further research on the anticancer role of Lf, which ultimately will contribute to its safer and more rational application in the human therapy of these life-threatening cancers.